2007
DOI: 10.4049/jimmunol.178.4.2328
|View full text |Cite
|
Sign up to set email alerts
|

Requirement for Phosphoinositide 3-Kinase p110δ Signaling in B Cell Antigen Receptor-Mediated Antigen Presentation

Abstract: The BCR serves to both signal cellular activation and enhance uptake and presentation of Ags by B cells; however, the intracellular signaling mechanisms linking the BCR to Ag presentation functions have been controversial. PI3Ks are critical signaling enzymes controlling many cellular processes, with the p110δ isoform playing a critical role in BCR signaling. In this study, we used pharmacological and genetic approaches to evaluate the role of p110δ signaling in Ag presentation by primary B lymphocytes. It was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
39
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
4

Relationship

5
4

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 56 publications
(76 reference statements)
5
39
0
Order By: Relevance
“…Our results suggest that Bam32-deficient GC B cells are unable to promote CD4+ T cell accumulation within established GCs, a function recently shown to depend on cognate B:T interactions (32). We have found that PI3K is required for efficient BCR-mediated Ag presentation and formation of stable B:T conjugates (37), consistent with the model that signaling through this pathway promotes B:T cognate interactions within GCs. Our recent results indicate that Bam32 is also required for efficient BCR-mediated Ag presentation, likely via its role in promoting Rac activation and B cell adhesion to ICAM (M. Al-Alwan, S. Hou, T. Zhang, K. Makondo, and A.J.…”
Section: Discussionsupporting
confidence: 76%
“…Our results suggest that Bam32-deficient GC B cells are unable to promote CD4+ T cell accumulation within established GCs, a function recently shown to depend on cognate B:T interactions (32). We have found that PI3K is required for efficient BCR-mediated Ag presentation and formation of stable B:T conjugates (37), consistent with the model that signaling through this pathway promotes B:T cognate interactions within GCs. Our recent results indicate that Bam32 is also required for efficient BCR-mediated Ag presentation, likely via its role in promoting Rac activation and B cell adhesion to ICAM (M. Al-Alwan, S. Hou, T. Zhang, K. Makondo, and A.J.…”
Section: Discussionsupporting
confidence: 76%
“…Moreover, the migration of MZ B cells to the pancreatic lymph node, where they present self-Ags to autoreactive T cells, has been implicated in the development of diabetes in NOD mice (59). IC87114 effectively blocks the ability of B cells to present Ags and activate T cells (18). These data, together with our findings that IC87114 reduces both CXCL13-induced MZ B cell migration and TLR-induced Ab production by MZ B cells, suggest that p110␦ inhibitors could reduce the ability of MZ B cells to traffic to other organs and contribute to autoimmune diseases.…”
Section: Discussionmentioning
confidence: 99%
“…For conventional B-2 cells, activation of the PI3K signaling pathway by chemokine receptors, the BCR, cytokine receptors, and TLRs plays an important role in their development, their trafficking and Ag presentation functions, their activation and proliferation, and their ability to differentiate into Ab-producing cells (17)(18)(19)(20)(21). Although B cells express all four isoforms of the class I PI3K p110 catalytic subunit (22), the p110␦ isoform, which is expressed primarily in hematopoietic cells, appears to be the most important for B cell development and activation.…”
mentioning
confidence: 99%
“…We recently found that activity of the p110d isoform of PI3K is required for efficient BCR-mediated Ag presentation (24). PI3K signaling is not required for BCR endocytosis or association with late endosomes but is required for Ag-pulsed B cells to form conjugates with cognate T cells.…”
mentioning
confidence: 99%